The Contest for Moral Politics: Interrogating the Cultural Politics of Malaysian Cultural Groups - Soon Chuan Yean (Kajian Malaysia, 2011)
This paper argues that the studies of post-2008 Malaysian political structures have overlooked the cultural politics articulated by artists, film makers, cartoonists, musicians, committed social actors and academicians. Their languages of politics do not manifest into ideologies or policies of political parties, but the construction of ideas, non-official histories, life stories and alternative citizenry re-construct the moral politics that the regime of Barisan Nasional (BN), the ruling party, has failed to provide. This political terrain has begun forming within the Malaysian society since the 1970s and became more critical and overt during the 1998 Reformasi period. Following the changing (political) nature of Malaysian civil society groups and the 'opening up' of spaces for more freedom of expression, this political terrain elevated to a new height in 2008.